Doing laboratory ethnography: reflections on method in scientific workplaces. (April 2017) - Stephens, Neil; Lewis, Jamie
Laboratory ethnography extended the social scientist's gaze into the day-to-day accomplishment of scientific practice. Here we reflect upon our own ethnographies of biomedical scientific workspaces to provoke methodological discussion on the doing of laboratory ethnography. What we provide is less a 'how to' guide and more a commentary on what to look for and what to look at. We draw upon our empirical research with stem cell laboratories and animal houses, teams producing robotic surgical tools, musicians sonifying data science, a psychiatric genetics laboratory, and scientists developing laboratory grown meat. We use these cases to example a set of potential ethnographic themes worthy of pursuit: science epistemics and the extended laboratory, the interaction order of scientific work, sensory realms and the rending of science as sensible, conferences as performative sites, and the spaces, places and temporalities of scientific work.